2022
DOI: 10.1001/jamacardio.2022.0193
|View full text |Cite
|
Sign up to set email alerts
|

Validating Deep Learning to Distinguish Takotsubo Syndrome From Acute Myocardial Infarction—Beware of Shortcuts, Human Supervision Required

Abstract: Artificial intelligence, particularly deep learning (DL), is poised to transform the field of cardiovascular imaging. While still a relatively young discipline, there has been an explosion of research in DL for cardiovascular imaging as investigators seek to build systems designed to segment cardiac chambers, automate functional assessment, detect disease states, and predict prognosis-all using raw imaging data. [1][2][3] Innovative systems have been designed to guide a novice to obtain diagnostic bedside card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Deep learning could be applied to LV flow fields for disease identification, similar to reported analyses of structural images (Tromp et al, 2022;Wehbe et al, 2023) . Contrastive POD (cPOD) could remove background LV flow features shared by healthy and diseased subjects, potentially improving cohort separability or identify subpopulations in DCM or HCM (Abid et al, 2018).…”
Section: Limitations and Future Workmentioning
confidence: 98%
“…Deep learning could be applied to LV flow fields for disease identification, similar to reported analyses of structural images (Tromp et al, 2022;Wehbe et al, 2023) . Contrastive POD (cPOD) could remove background LV flow features shared by healthy and diseased subjects, potentially improving cohort separability or identify subpopulations in DCM or HCM (Abid et al, 2018).…”
Section: Limitations and Future Workmentioning
confidence: 98%
“…Several studies have shown how the use of AI Echo can minimize the known limitations of these approaches. 40–42,44,47,50,51…”
Section: Ai Echo For Image Interpretationmentioning
confidence: 99%
“…Thus, it is critical to assess final model performance on a separate holdout test set (preferably from an external source) that the model was never exposed to during the entire research and development process (eAppendix 6 and eTable 3 in the Supplement). Failure to do so can result in falsely optimistic performance estimates and/or failure to recognize a model that has overfit to irrelevant features called shortcuts (eg, scanner metadata or manufacturer logos) . Detailed guidance on the design, implementation, and evaluation of DL models for CVI have been previously published as part of the Proposed Requirements for Cardiovascular Imaging-Related Machine Learning Evaluation (PRIME) checklist …”
Section: Training and Evaluating A Deep Learning Modelmentioning
confidence: 99%